FUNGSI BAHASA DALAM WACANA IKLAN MEDIA CETAK - sri puji astuti (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2012)
Advertisement is a tool to convey a message from the produser to the consumer. Advertisement has a very important power as a marketing tools that helps selling things or services.The function of advertisement is to affect people buying things or use the service that the producer produced. Advertising language is included in business variety and one of the language which is used in communication. What kind of communication function includes in a printed media discourse which is discussed in this working paper. This research data source comes from Suara Merdeka , Jawa Pos newspaper, and Femina magazine. The research method which is used is a descriptive method. Based on the research result it was found the six language functions in a discourse of printed media . they are the expressive function, directive function, informational function, metalingual function, poetic function, and imaginative function. Key word : Language function, advertisement, printed media